Uso de 2-octil cianoacrilato em anastomose colônia:estudo experimental em ratos Wistar - Cleber Soares Junior (2008)
The aim of the present study was to compare the effect of 2-octyl cyanoacrylate tissue adhesive with polypropylene suture on the healing of colonic anastomosis in wistar rats. Thirty two animals, divided in four groups of eigth, were established concerning suture with Polypropylene (P) or Cyanoacrylate (C) application, and the day chose for euthanasia: third or seventh day following operation (P3, C3, P7, C7). Following laparotomy, colotomy was performed five centimeters from the ileocecal valve. In the control group, the anastomosis was done in a singlelayer with 5.0 polypropylene interrupted extramucosal sutures. In the adhesive group, the anastomosis was performed by using 2-octyl cyanoacrylate without any suture support. Integrity and gross anastomotic healing, existence of intraabdominal abscess or peritonitis, mechanical strength (bursting pressure), intestinal obstruction, adhesions formation, histological healing and inflammatory process were recorded. Anastomoses were resected including 1.5 cm of bowel on either side after adhesions formation assessment. Bursting pressure wasmeasured in cm H2O and intestinal obstruction was evaluated before histological examination. Anastomotic dehiscence, intra-abdominal abscess and peritonitis did not occur in any group. Adhesion formation was more extensive in the cyanoacrylate group on the seventh postoperative day comparing with suture group (p=0.007). There was no difference in the third day regarding bursting pressure (p=0.081). However, the mechanical strength of the anastomosis assessed on the seventh postoperative day was lower in 2-octyl cyanoacrylate group (p=0.002). Partial intestinal obstruction rate were more frequent inanastomosis using 2-octyl cyanoacrylate compared to those with polypropylene suture on the seventh postoperative day (p=0.029). Operative time were longer in groups with adhesive (p=0.004). The wound healing process, as assessed by inflammatory cell infiltration, blood vessel neodevelopment, collagen deposition, fibroblast activity and muscular hypertrophy, did not differ statistically between groups (p>0.05). The application of 2-octyl cyanoacrylate, under experimental conditions, did not provide any benefit over conventional suturing at the third day.The adhesive seems to be detrimental at the seventh day of the healing, causing intense adhesion formation, colonic obstruction; and impairment healing with less mechanical strength resistance.